The influence of magnetic field on the growth of tomato (Lycopersicum esculentum) infected with Fusarium oxysporum - Rochmah Agustrina; Endang Nurcahyani; Eko Pramono; Ika Listiana; Eko Nastiti (Universitas Lampung, 2016)
Abstract— This Previous research suggests that magnetic field (MF) can enhance seedling vigor, growth, and the production of tomato plants. This study examines the influence of MF on the growth of tomato infected by Fusarium oxysporum, fungal pathogen that causes Fusarium wilt in tomatoes. This factorial study arranged in a stripe split plot design. Factors tested consists of long exposure to the MF, M (control; 7'48